THE ELECTRIC POWER INDUSTRY A NONTECHNICAL GUIDE - Miesner, Thomas O.; Gallo, Andrew (PennWell Books, 2022)
Covering generation to distribution, this book provides a practical guide to the electrical power industry, with a special focus on renewables - their opportunities and challenges. Starting with an explanation of electricity, how it works, and why it works that way, the book moves on to a history of the industry that generates, transmits, and distributes electricity. The book also covers the materials, hardware, and instruments the industry uses, and how utilities construct, operate, and maintain "the grid" encompassing control rooms, wide area controls, and cybersecurity. The final chapters explain regulations, grid reliability, markets, and the challenges the industry faces in the future